NUMERICAL ABUNDANCE OF BENTHIC MACROINVERTEBRATES IN SELECTED RESERVOIRS OF TAMIL NADU - Manoharan, S; MURUGESAN, V K; Palaniswamy, Rani (Journal of the Inland Fisheries Society of India, 2016)
Richness and diversity of benthic macroinvertebrates in nineteen reservoirs located at different river basins of Tamil Nadu were investigated. Krishnagiri reservoir recorded the highest macrobenthic population (4290 u/m2) followed byWillington (4170 u/m2). Gunderipallam, Varattupallam, Amaravathy, Uppar, Vaigai, Pechiparai and Vidur reservoirs also recorded large quantity of macrobenthos (1926 to 2338 u/m2). Palar-Poranthalar, Pilloor, Vembakottai, Manimuthar and Orathupalayam exhibited a moderate quantity of macrobenthos (952 to 1458 u/m2). A low level of bottom fauna was encountered at Parambikulam (502 u/m2), Thoonakadavu (838 u/m2), Peruvaripallam (329 u/m2), Uppar (411 u/m2) and Odathurai (364 u/m2). While Chironomus larvae formed the major portion of the macrobenthos (2835 u/m2) at Krishnagiri,molluscan forms dominated (3939 u/m2) at Willington reservoir.